Adsorption of Phenol using Cellulose and Hydrochar: Kinetic, Isotherm, and Regeneration Studies - Sahrul Wibiyan; Alfan Wijaya; Patimah Mega Syah Bahar Nur Siregar (Indonesian Journal of Material Research, 2023)
In this study, hydrocarbons were obtained through the hydrothermal carbonization synthesis method. The XRD data of the cellulose sample revealed 2θ angles of 15.46°, 22.34°, and 34.36°, indicating that the cellulose sample under investigation had an amorphous structure. The XRD data of the hydrocarbon sample showed a 2θ angle of 25.72°, indicating the presence of graphitic carbon. The FTIR spectra of both cellulose and hydrocarbon exhibited similarities at wave numbers 3394 cm-1, 2893 cm-1, 1662 cm-1, 1000-1200 cm-1, and 847 cm-1. BET analysis revealed that the hydrocarbon material surface area measured was 7.366 m²/g, measured pore volume for the entire sample was 0.008 cc/g, and the average size of the pores was 3.189 nm. The optimal pH variation for cellulose was at pH 10, with an adsorption capacity of 10.75 mg/g, on the other hand, was tested at pH 6 and demonstrated an adsorption capacity of 12.74 mg/g. The adsorption kinetics model for both adsorbents was PSO, and the adsorption isotherm model was Freundlich. Cellulose exhibited a maximum adsorption capacity of 35.336 mg/g, while hydrochar demonstrated a maximum adsorption capacity of 21.008 mg/g. It is noteworthy that both adsorbents were capable of being reused for up to five cycles.